Expressões das violências de gênero no cotidiano de terapeutas ocupacionais no campo da saúde - Farias, Aline Zacchi (2021)
The patriarchal social structure produces modes of subjectivation that reduce women's possibilities of choice and sustain individual and collective violence in everyday life. This research starts from the Keleman idea of “bodies/experiences”, as a vital motion to exist, comprising the Occupational Therapy-body, a predominantly female profession, to portray the gender violence experienced by occupational therapists. The objective was to understand the perceptions of women occupational therapists, working in health services, about gender violence in their everyday lives, utilizing the methodological framework of cartography and theoretical assumptions from feminist epistemologies. Sixty-seven responses from occupational therapists were analyzed among 1018 respondents to a remote questionnaire produced by the Adelaides collective in a research on experiences of gender violence in Brazil experienced by women in the field of Public Health. The questionnaire was organized in five sections (socioeconomic data; professional and academic experience; social engagement and political activism; experiences involving sexism and violence; maternity) with narrative and multiple choice questions. Numerical data were analyzed using simple statistics and qualitative data using the analytical technique of translating the narratives, which involves the analysis of what can be commonly perceived in a set of signs, symbols, practices, and processes situated in the experiences. The results indicate that 91% of the participants suffered some violence for being a woman in their home, study, work and/or public environments. The coping strategies used were organized into five actions: training, researching, politicizing, disrupting and caring. We conclude that everyday life presents itself as a potential means of expressions, visible or invisible, of human action, whether violent or denunciation actions, assuming aspects of reproduction or transformation of established relationships, such as those embedded in the culture of violence to which women are submitted.